The Effectiveness Of A Proposed Educational Unit Based On The Comprehensive Language Approach In Developing Reading Skills Among Foreign Learners At The Intermediate Level/ فاعلية وحدة تعليمية مقترحة قائمة على المدخل الكلي للغة في تنمية مهارة القراءة لدى الدارسين الأجانب في المستوى المتوسط - Abdur Razaq, Kharashi Nasirudeen; Mohd Noor, Siti Salwa Binti (Ijaz Arabi Journal of Arabic Learning, 2024)
This study aimed to determine the effectiveness of a proposed educational unit in light of the Whole Language approach in developing some Arabic language arts skills among foreign learners at the intermediate level. To achieve this goal, the researcher built research tools consisting of indicators of necessary Arabic language arts skills for foreign learners at the intermediate level. Method: a pre-and post-test will be used to develop appropriate Arabic language arts skills among foreign learners at the intermediate level. The study sample consisted of thirty male and female students from the preparatory year program at the Language Center of the Faculty of Languages and Communication at Sultan Zainal Abidin University, Kuala Terengganu, Malaysia. The researcher adopted the descriptive and quasi-experimental method when applying the study tools. After experimenting with the study tools and analyzing the results (data) of the pre-and post-applications statistically using statistical packages system of social sciences to calculate percentages, relative weight, and standard deviation, the study reached results, the most important of which are: (1) The effectiveness of the proposed educational unit built in the light of whole approach in developing Arabic language arts skills as a whole. (2) The effectiveness of the proposed educational unit is built in the light of the whole approach to developing language skills in each skill area separately. According to its results, the study also suggested some recommendations and proposals, the most important of which are: (1) The need to adopt the Whole language approach in developing the reading skills of Arabic language learners, whether native or non-native speakers. (2) The importance of sensitizing Arabic language teachers to the importance of this approach and providing training to familiarize them with the application of this approach. (3) This approach is used in teaching other language skills because it positively impacts the teaching of the Arabic language.